Inventory of Insects in Land Water Spinach Cultivation Using the Insecticide Abamectin - Mahmud, Yusmar; Deyanti, Silvi; Solfan, Bakhendri; Zam, Syukria Ikhsan; Oksana, Oksana (Mulawarman University, 2026)
Land kale in a cultivated has an obstacle, namely the presence of insects. Based on their there are beneficial and harmful insects. To deal with harmful insects, insecticides are used which contain the active ingredient abamectin which causes insect skin irritation and eliminates appetite. The aim of this research was to see the presence of insects in the use of abamectin in land kale plantings in West Sidomulyo Village. This study was conducted in May and September 2024 in West Sidomulyo Village and identification was carried out at the Pathology Laboratory, Entomology, Microbiology, and Soil Science, Faculty of Agriculture and Animal Science, Sultan Syarif Kasim State Islamic University, Riau. The samplin was by catching directly using nets and yellow traps found on land kale plants. Insects are stored in collection bottles. The research results showed that there were 3 ordo, 7 family dan 8 genera of insects. There are 4 insect pests namely Anasa sp., Gonocerus sp., Bemisia sp., and Aspidimorpha sp., there are 3 predatory insect namely Verenia sp., Menochilus sp., and Paederus sp., and there 1 migrant insect namely Musca sp. The insects found have haustelata (piercin, sucking) and mandibulata (biting, chewing) mounth types. The intensity of insect pest attack increased after the application of abamectin insecticide, allegedly due to the inappropriate application time, where the application was carried out in the morning toward noon with a fairly high temperature so that evaporation occured and the effectiveness of the insecticide was reduced.